2021
DOI: 10.1002/smll.202005745
|View full text |Cite
|
Sign up to set email alerts
|

Iron Selenide Microcapsules as Universal Conversion‐Typed Anodes for Alkali Metal‐Ion Batteries

Abstract: Rechargeable alkali metal‐ion batteries (AMIBs) are receiving significant attention owing to their high energy density and low weight. The performance of AMIBs is highly dependent on the electrode materials. It is, therefore, quite crucial to explore suitable electrode materials that can fulfil the future requirements of AMIBs. Herein, a hierarchical hybrid yolk–shell structure of carbon‐coated iron selenide microcapsules (FeSe2@C‐3 MCs) is prepared via facile hydrothermal reaction, carbon‐coating, HCl solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 65 publications
5
36
0
Order By: Relevance
“…[52] In Se3d spectra (Figure 6f), new peaks at 52.5 eV (Se 3d5/2) and 53.4 eV (Se 3d3/2) are deconvolved when discharged to 0.01 V, which corresponds to the formation of potassium-selenium compound. And the peaks at 53.9 (Se 3d5/2) and 54.8 (Se 3d3/2) for Fe-Se reappear after full discharge to 3.0 V. [16] The electrochemical conversion mechanism can be described by the following equations:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[52] In Se3d spectra (Figure 6f), new peaks at 52.5 eV (Se 3d5/2) and 53.4 eV (Se 3d3/2) are deconvolved when discharged to 0.01 V, which corresponds to the formation of potassium-selenium compound. And the peaks at 53.9 (Se 3d5/2) and 54.8 (Se 3d3/2) for Fe-Se reappear after full discharge to 3.0 V. [16] The electrochemical conversion mechanism can be described by the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] Iron selenides, as one typical metal selenide, have metallic properties as well as flexible valence states, which have been extensively investigated as anode materials for K + /Na + storage. [16,17] They still suffer from, however, volume expansion and poor conductivity, which lead to structural instability of the electrode and further result in poor cycling performance upon repeated insertion and extraction of K + /Na + ions. [18,19] Thus, numerous strategies have been proposed.…”
mentioning
confidence: 99%
“…However, the existence of the reaction intermediate K 2 Se 2 is yet to be explained, and further efforts are required to explore its origin. In contrast to the electrochemical reaction mechanism of the insertion of K + into FeSe 2 /NC, a study on a hierarchical hybrid yolk–shell FeSe 2 @C performed by Wu et al reported that elemental selenium was not formed during cycling. They carried out in situ XRD and XPS to monitor the reaction process of K + storage.…”
Section: Battery-type Anode Materialsmentioning
confidence: 98%
“…FeS 2 @NC nanosheets 1 M KFSI in EC/DEC (1/1) 525.5 at 100 A g −1 90% after 100 cycles (0.5 A g −1 ) [111] ZnSe/C 1 M KFSI in EC/DEC (1/1) 318 at 50 mA g −1 92% after 1000 cycles (0.5 A g −1 )…”
Section: Development Of Electrolytes For Graphitementioning
confidence: 99%